Entre a liberdade e a virtude: pensamento social e político de Michael Oakeshott - Cardoso, Felipe Gava (2018)
The thesis investigates Oakeshott's complete work and aims to analyze the nature of his conservative "disposition", taking into account his skeptical postulate and its theoretical roots, its contribution to social and political thought and its relation to the intellectual production of liberals and conservatives. The review of his arguments allows us to observe qualities and weaknesses in his approach to topics such as the epistemological foundations of knowledge, the attributes of individual consciousness, modes of conduct and civil society, the role of conversation in human fulfillment, the ideological fields and their patterns, the function and framework of the state, among others. These include concepts such as "conservative disposition", "reflexive consciousness", "conversation", "civil association", and "politics of faith". This appraisal evidences that Oakeshott transits on the edge of conservative and liberal thinking in a permanent tension. The comparison with liberal authors reveals a thinker that is constantly concerned with the preservation and use of the valuable habits of Western heritage. On the other hand, dialogue with conservatives highlights his emphasis on the role of individual freedom in the conduct of their own existence. Those are the sources of his originality and vulnerability.